Peer trainers compared with basic life support trainers in delivering effective cardiopulmonary resuscitation training to secondary school students - Sabihah A,; Shamsuriani Md Jamal,; Fadzlon MY,; Mohd Hisham Mohd Isa,; Afliza Abu Bakar,; Siti Nidzwani Mohamad Mahdi,; Tan, TL; Dazlin Masdiana Sabardin,; Emilia MR,; Nik Azlan NM, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Teaching cardiopulmonary resuscitation (CPR) skills to the public is essential in improving cardiac arrest survival. American Heart Association suggested to incorporate it into the school curriculum. Peer trainers is a low cost and effective method in achieving this. The objective of this 3 months prospective controlled study was to compare the effectiveness of teaching compression only CPR between peers and certified basic life support (BLS) trainers to secondary school students. Improvement in knowledge and psychomotor skills of CPR compression were the primary outcome evaluated. Twelve peer trainers aged 16-years-old and twelve certified BLS trainers were recruited into the study. Compression only CPR was taught to 36 randomized secondary school students by either peer trainers (Group P) or BLS trainers (Group B). A pre-test, immediate post-test and 3 months retention test on knowledge and psychomotor skill were conducted. There was no statistically a significant difference in the mean scores of knowledge and psychomotor at pre-test, post-test and 3 months retention between Group P and Group B. There was significant increase of knowledge score between pre-test and post-test in Group P (mean difference 5.8+2.7, p<0.001) and in Group B (mean difference 4.7+2.7, p<0.001). Psychomotor score was significantly increased between pre-test and post -test in Group P (mean difference 7.11+1.49, p<0.001) and Group B (mean difference 7.22+1.5, p<0.001). Peer trainers is non-inferior to BLS trainers in teaching CPR to secondary school students as both groups showed significant improvement at post-test.